Pemanfaatan Probiotik untuk Budidaya Perikanan - Fitria Rahmayanti; Mahendra Mahendra; Munandar Munandar; Citra Dina Febrina; Endah Anisa Rahma (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
Probiotics application in aquaculture sector has been promoted since the government has banned antibiotics application in aquaculture sector. Probiotics are very useful in aquaculture because it can accelerate fish growth, improve fish health, and maintain water quality in good condition. However, there are many fish farmers who do not know the advantages, manufacturing techniques and the application of probiotics to support aquaculture activities. Therefore, we have conducted this community service for fish farmers in Meunasah Sukon Village, Lembah Sabil District, Southwest Aceh Regency. This community service is carried out through counseling by describing the benefits of probiotics, followed by discussions with participants and probiotics practice using natural ingredients that are easily available. The result showed that the level of understanding and knowledge of fish farmers in this village about the benefits of probiotics, how to manufacture and its application were increases after this community service was conducted. The activities of enhancement fish farmer capacities are needed to improve their abilities about information on aquaculture renewable technology.